(a)f'(x)+g'(x)=f(x)-g(x)+g(x)-f(x)=0
so [f(x)+g(x)]'=0
f(x)+g(x)=C
f(0)+g(0)=C=5+1=6
sof(x)+g(x)=6
(b)plug in g(x)=6-f(x) to the first equation
f'(x)=f(x)-(6-f(x))
f'(x)=2f(x)-6
那就分离变量
df/dx=2f-6
df/(f-3)=2dx
两边积分
ln(f-3)=2x+C'
f-3=e^(2x+C')
f=3+Ce^(2x)
代入x=0,f=5
C=2
f=3+2e^(2x)
g=6-f=3-2e^(2x)
f'(x)-2f(x)=-6
multiply both sides by e^(-2x) (积分因子)
e^(-2x)f'(x)-2e^(-2x)f(x)=-6
左边等价于
e^(-2x)f'(x)+(e^(-2x))'f(x)=(e^(-2x)f(x))' (导数的积法则倒过来)
(e^(-2x)f(x))'=-6e^(-2x)
so
e^(-2x)f(x)=∫-6e^(-2x)dx
=3e^(-2x)+C
f(x)=3+Ce^(2x)
plug in x=0,f(0)=5
3+C=5,C=2
so
f(x)=3+2e^(2x)
g(x)=3-2e^(2x)